Supporting Children with Speech, Language, and Communication Needs in Indonesian Kindergarten Classrooms - Indri Hapsari (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This article provides a perspective on how children with speech, language, and communication needs (SLCN) in Indonesia are identified and supported in the classrooms. A narrative review of the extant peer-reviewed articles was adopted as the research method. Informed by the SANRA (Scale for the Assessment of Narrative Review Articles) protocol, 6 databases were searched, 214 articles published between 2011 - 2022 were identified, and 6 articles published between 2018 - 2022 were selected for analysis. The findings show that the identification of children with SLCN relied on general teacher observations instead of formal measurements. Children with SLCN were mostly supported by teachers through strategies such as modelling correct speech sounds, singing and storytelling. Researchers described SLCN using the terms ‘speech’ and ‘language’ without differentiation. There remains a scarcity of research about SLCN in Indonesia. This narrative review aims to provide recommendations for the future of SLCN research in Indonesia